Correlation between sclerostin and Dickkopf-1 with aortic arterial stiffness in patients with type 2 diabetes: A prospective, cross-sectional study. (May 2019) - Yang, Hsin-Yu; Wu, Du-An; Chen, Ming-Chun; Hsu, Bang-Gee
Background: Sclerostin and Dickkopf-1 are extracellular inhibitors of the canonical Wnt/β-catenin signalling pathway, which is implicated in the development of arterial stiffness. However, the correlation between aortic stiffness and sclerostin or Dickkopf-1 levels in patients with type 2 diabetes mellitus is unknown. Methods: Fasting blood samples were collected from 125 patients with type 2 diabetes mellitus. Aortic stiffness was measured by carotid–femoral pulse wave velocity, and high aortic stiffness was defined by a carotid–femoral pulse wave velocity of >10 m/s. The serum sclerostin and Dickkopf-1 concentrations were determined using commercially available enzyme-linked immunosorbent assays. Results: In total, 46 patients with type 2 diabetes mellitus (36.8%) had high levels of aortic stiffness. Compared to the control group without aortic stiffness, this group was significantly older, had higher systolic and diastolic blood pressures, had higher blood urea nitrogen, creatinine, urinary albumin-to-creatinine ratio and serum sclerostin levels, and had significantly lower high-density lipoprotein cholesterol levels and estimated glomerular filtration rates. After adjusting for confounders, serum sclerostin [odds ratio = 1.005 (1.002–1.007), p = 0.002] levels remained an independent predictor of aortic stiffness. Multivariate analysis showed that the serum sclerostin level ( β = 0.374, adjusted R 2 change = 0.221, p < 0.001) was positively associated with carotid–femoral pulse wave velocity. Conclusion: Serum levels of sclerostin, but not Dickkopf-1, are positively correlated with carotid–femoral pulse wave velocity and independently predict aortic stiffness in patients with type 2 diabetes mellitus.